Production of biofuels from pine needle via catalytic fast pyrolysis over HBeta - Kim, Young-Min; Lee, Hyung Won; Jang, Seong Ho; Jeong, Jaehun; Ryu, Sumin; Jung, Sang-Chul; Park, Young-Kwon (The Korean journal of chemical engineering, 2020)
The thermal and catalytic pyrolysis of pine needles over HBeta catalysts with different SiO 2 /Al 2 O 3 ratios (25 and 300) were investigated by thermogravimetric analysis (TGA) and pyrolyzer-gas chromatography/mass spectrometry. TGA showed that the main decomposition of pine needles occurred between 150 and 550 °C. The catalytic DTG curves revealed the same decomposition temperature region as the non-catalytic TG curve of pine needles. Pyrolyzergas chromatography/mass spectrometry suggested that the effective catalytic conversion of pyrolyzate intermediates and other hydrocarbons to aromatic hydrocarbons can be achieved using HBeta catalysts at 600 °C. HBeta(25) produced a larger amount of aromatic hydrocarbons than HBeta(300) because of its higher acid amounts. By increasing the reaction temperature from 500 to 700 °C, the formation of benzene, toluene, ethylbenzene, xylenes (BTEXs) and other polycyclic aromatic hydrocarbons was increased with a concomitant decrease in phenolics and other oxygenates. The formation efficiency of BTEXs was increased further by increasing the catalyst loading.